2022
DOI: 10.1093/oncolo/oyac129
|View full text |Cite
|
Sign up to set email alerts
|

Alarming Drop in Early Stage Colorectal Cancer Diagnoses After COVID-19 Outbreak: A Real-World Analysis from the Italian COVID-DELAY Study

Abstract: Background Coronavirus disease 2019 (COVID-19) has triggered the disruption of health care on a global scale. With Italy tangled up in the pandemic response, oncology care has been largely diverted and cancer screenings suspended. Our multicenter Italian study aimed to evaluate whether COVID-19 has impacted access to diagnosis, staging, and treatment for patients newly diagnosed with colorectal cancer (CRC), compared with pre-pandemic time. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 38 publications
3
15
0
Order By: Relevance
“…In this meta-analysis, perioperative blood loss was significantly greater in the COVID-19 groups than in the pre-COVID-19 groups, possibly due to the lack of colonoscopy, the cancer stage may be more advanced during the epidemic. 60 However, no significant difference was found in the number of blood transfusions between groups. Due to the small sample size of perioperative blood loss, more studies should be included in the future.…”
Section: Discussionmentioning
confidence: 87%
“…In this meta-analysis, perioperative blood loss was significantly greater in the COVID-19 groups than in the pre-COVID-19 groups, possibly due to the lack of colonoscopy, the cancer stage may be more advanced during the epidemic. 60 However, no significant difference was found in the number of blood transfusions between groups. Due to the small sample size of perioperative blood loss, more studies should be included in the future.…”
Section: Discussionmentioning
confidence: 87%
“…Further GSEA analysis showed that in high ZBTB9 expression samples, the G2M checkpoint, epithelial-mesenchymal transition, E2F targets, and KRAS-related signaling pathways were significantly activated, which has been reported to participate in tumor proliferation and progression [36,37]. In addition, the investigation of the correlation between ZBTB9 and KRAS signaling pathway demonstrated that ZBTB9 was evidently associated with MAPK1, NRAS, SHP2, SOS1, and KRAS2 (all play imperative roles in KRAS pathway [38][39][40]), suggesting that the malignant biological behaviors under ZBTB9 upregulation were probably mediating through this pathways. Blocking of ZBTB9 could have the potential value to optimize the efficacy of inhibitors against KRAS signaling pathways [41,42].…”
Section: Discussionmentioning
confidence: 97%
“…As such, we reported the same experience by not prolonging the interval between diagnosis and surgery for the time period analyzed over a mean time of 15 days. However, several reports, from Spain, Japan, and other countries [ 29 , 30 , 31 , 32 ] described a generalized increase in stage III and IV tumors during the pandemic. We could not find any differences in stage at presentation nor in histopathological data between groups ( Table 2 , Table 3 and Table 4 ), but the subgroup analysis showed, only for left colon tumors, an increase of almost double for stage II cancers and a drop in stage I.…”
Section: Discussionmentioning
confidence: 99%